STUDI TENTANG PERBEDAAN BERAT BADAN ANTARA MANULA DENGAN KEHILANGAN GIGI-GELIGI POSTERIOR BILATERAL FREE-END DAN MANULA YANG MASIH MEMILIKI GIGI GELIGI POSTERIOR DI KELURAHAN CAMPLONG I - APRI ADIARI MANU; MELKISEDEK O. NUBATONIS; RATIH VARIANI (JURNAL INFO KESEHATAN, 2014)
Lose part or all of the teeth can cause emotional effects, both systemic and functional. Functional impact of tooth loss that can lead to a decrease in masticatory function and subsequently cause a lack of nutrition for the body. Loss of teeth can also affect public health and the oral cavity that will affect the overall quality of life. Decreased masticatory function can result in weight loss, as well the possibility of other factors associated with the taste of that influence appetite, reduced muscle coordination, poor physical conditions, social and economic factors, as well as food absorption factor (absorption capacity). Occlusion is less well as loss of contact back teeth causing dental occlusion can not perform optimally function in chewing which causes the difficulty and limitations of mastication. Difficulties and limitations is what makes people choose softer foods and avoid eating foods that contain lots offiber just as vegetables and fruits. Difficulty in chewing food semakain increase along with the increasing number of missing teeth, especially in theposterior part. This research is analytic study with cross-sectional design to describe the weight ratio between the Seniors with loss of Posterior Teeth Bilateral Free-End and Seniors who still have teeth Posterior aged 60-75. The population in this study were all people aged 60-75 years who have lost posterior teeth Bilateral Free-end and which still has a posterior teeth in the village Camplong I. The samples in this study were taken with Consecutive sampling method. The sample size in this study are 28 people with the details; Group I: sample totaled 13 and Group II: sample totaled 15 people. The results of this study are: when a soft-textured food consumed then there is no difference in the average weight loss in the elderly with teeth posterior free-end and seniors who still have a posterior teeth. When the hard-textured food consumed then there is the difference in average Weight loss in the elderly with posterior teeth free-end and seniors who still have a posterior teeth.